PREGNANCY WITH PRIMARY SCLEROSING CHOLANGITIS - E. A. Alexandrova; E. Z. Burnevich; E. A. Arion (Акушерство, гинекология и репродукция, 2016)
Primary sclerosing cholangitis (PSC) is autoimmune disease characterized by inflammation and sclerosis of the bile duct, which leads to the development of secondary biliary cirrhosis. Many women with primary sclerosing cholangitis are at reproductive age (mean age of onset is 40 years old, but the cases of the disease in other age groups were described). There is a risk of negative impact of primary sclerosing cholangitis in the mother (exacerbation PSC) and the fetus (intrauterine fetal hypoxia, premature birth), but overall prognosis for the mother and child is favorable (if pregnant does not have cirrhosis of the liver complications). Pregnant women with varicose veins of the esophagus have a high maternal mortality. Ursodeoxycholic acid is the drug of choice for the treatment of pruritus in pregnant women with primary sclerosing cholangitis